Pengaruh Inflasi, Nilai Tukar, Suku Bunga, Dan Volume Transaksi Terhadap Harga Saham Perusahaan Pada Kondisi Pandemi Covid-19 - Serena Sila Sebo; Moch Nafi (University of Merdeka Malang, 2020)
This study aims to determine the effect of inflation, exchange rates, interest rates, and transaction volume on stock prices of companies in the food and beverage sector. The method used in this research is quantitative method with multiple linear analysis. In this study using 5 samples of food and beverage sector companies listed on the IDX in the period March-September 2020 based on certain criteria. The results of the study found that partially inflation, exchange rates, and interest rates have no significant effect on stock prices, while transaction volume has a positive and significant effect on stock prices. The research results simultaneously state that inflation, exchange rates, interest rates and transaction volume have a significant effect on stock prices. DOI: 10.26905/ap.v6i2.5358